The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1039/d0ra00622j
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of Ni(OH)2/MWCNT nanocomposites for constructing a nonenzymatic hydroquinone/O2fuel cell

Abstract: In this work, a H-type hydroquinone/O2 fuel cell was assembled and shows high energy density in neutral phosphate buffer solution at moderate temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Wu et al reported the use of 2-D Ni(OH) 2 nanodisks deposited on multiwalled carbon nanotubes (MWCNTs) as an anodic catalyst of the hydroquinone biofuel cell (Figure 12a−d). 81 The poor conductivity of Ni(OH) 2 was complemented by bonding with MWCNTs, and the large specific surface area of MWCNTs significantly enhanced the ■ UTILIZATION OF EC-LOHC UNDER FUEL CELL SYSTEMS EC-LOHC has been utilized not only as a H 2 storage agent but also as a fuel for a low-temperature proton exchange membrane fuel cell (PEMFC). Among the various EC-LOHCs, only a few are directly applied to fuel cells, and most research has been focused on IPA/acetone.…”
Section: ■ Electrocatalysts For Ec-lohcmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al reported the use of 2-D Ni(OH) 2 nanodisks deposited on multiwalled carbon nanotubes (MWCNTs) as an anodic catalyst of the hydroquinone biofuel cell (Figure 12a−d). 81 The poor conductivity of Ni(OH) 2 was complemented by bonding with MWCNTs, and the large specific surface area of MWCNTs significantly enhanced the ■ UTILIZATION OF EC-LOHC UNDER FUEL CELL SYSTEMS EC-LOHC has been utilized not only as a H 2 storage agent but also as a fuel for a low-temperature proton exchange membrane fuel cell (PEMFC). Among the various EC-LOHCs, only a few are directly applied to fuel cells, and most research has been focused on IPA/acetone.…”
Section: ■ Electrocatalysts For Ec-lohcmentioning
confidence: 99%
“…A suggested way to immobilize nanoparticles is secondary bonding between 2-D materials and carbon nanotubes. Wu et al reported the use of 2-D Ni­(OH) 2 nanodisks deposited on multiwalled carbon nanotubes (MWCNTs) as an anodic catalyst of the hydroquinone biofuel cell (Figure a–d) . The poor conductivity of Ni­(OH) 2 was complemented by bonding with MWCNTs, and the large specific surface area of MWCNTs significantly enhanced the hydroquinone electro-oxidation kinetics.…”
Section: Electrocatalysts For Ec-lohcmentioning
confidence: 99%
See 1 more Smart Citation
“…14–16 Among the various catalysts based on transition metals, Ni(OH) 2 materials had been proven to be promising catalyst for GOR due to their unique layered structure with large interlayer spacing that allows the electrolyte diffusion within the catalyst layers resulting in a boosted catalytic activity. 17–20 Glucose can be oxidized into gluconolactone in the presence of Ni(OH) 2 according to the following eqn (1) and (2): 14 Ni(OH) 2 + OH − → NiOOH + H 2 O + e − 2NiOOH + Glucose → gluconolactone + 2Ni(OH) 2 …”
Section: Introductionmentioning
confidence: 99%
“…This divided cell is separated by a cation exchange membrane to shuttle ions as needed, ultimately allowing for the generation of current via the flow of electrons. Limited examples of fuel cells for comparable phenol oxidation have been reported, particularly in the context of wastewater remediation, and no such examples for cannabinoids or other comparably complex phenols are known. As a proof-of-concept, we targeted the development of an H-Cell-type fuel cell, as shown in Figure b.…”
mentioning
confidence: 99%